Konstruksi Sosial Makanan Sehat di Kalangan Pekerja Kesehatan Rumah Sakit Dr. Oen Surakarta - Ventilanova, Vinsensia; Trinugraha, Yosafat Hermawan; Zuhri, Saifuddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to analyze the social construction of healthy eating among healthcworkers at RS Dr. Oen Surakarta. Using a qualitative approach, the study explores the perceptions and practices related to healthy food among health workers at RS Dr. Oen Surakarta. The findings of the study indicate that the social construction of healthy eating among health workers at RS Dr. Oen Surakarta is influenced by factors such as organizational culture, work environment, and individual knowledge. The analysis reveals that practical needs, time constraints, and individual preferences have an impact on the choices and social construction of healthy food among health workers at RS Dr. Oen Surakarta. This study provides valuable insights into the social construction of healthy eating among health workers at RS Dr. Oen Surakarta and can serve as a basis for developing more effective health promotion programs in the workplace.